Uso de Microtomografía de rayos X para la identificación de daños en semillas de soja - Gallo, C. (2022)
Fil: Gallo, C. Instituto Nacional de Tecnología Agropecuaria. Estación Experimental Agropecuaria Oliveros (INTA); Argentina